Urban Stormwater Management in the United States - National Research Council (The National Academies Press, 2009)
The rapid conversion of land to urban and suburban areas has profoundly altered how water flows during and following storm events, putting higher volumes of water and more pollutants into the nation's rivers, lakes, and estuaries. These changes have degraded water quality and habitat in virtually every urban stream system. The Clean Water Act regulatory framework for addressing sewage and industrial wastes is not well suited to the more difficult problem of stormwater discharges. This book calls for an entirely new permitting structure that would put authority and accountability for stormwater discharges at the municipal level. A number of additional actions, such as conserving natural areas, reducing hard surface cover (e.g., roads and parking lots), and retrofitting urban areas with features that hold and treat stormwater, are recommended.
Keywords: Environment and Environmental Studies

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Communities in Action: Pathways to Health Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In the United States, some populations suffer from far greater disparities in health than others. Those disparities are caused not only by fundamental differences in health status across segments of the population, but also because of inequities in factors that impact health status, so-called determinants of health. Only part of an individual's health status depends on his or her behavior and choice; community-wide problems like poverty, unemployment, poor education, inadequate housing, poor public transportation, interpersonal violence, and decaying neighborhoods also contribute to health inequities, as well as the historic and ongoing interplay of structures, policies, and norms that shape lives. When these factors are not optimal in a community, it does not mean they are intractable: such inequities can be mitigated by social policies that can shape health in powerful ways. Communities in Action: Pathways to Health Equity seeks to delineate the causes of and the solutions to health inequities in the United States. This report focuses on what communities can do to promote health equity, what actions are needed by the many and varied stakeholders that are part of communities or support them, as well as the root causes and structural barriers that need to be overcome.
Keywords: Health and Medicine

Disaster Resilience: A National Imperative (The National Academies Press, 2012)
No person or place is immune from disasters or disaster-related losses. Infectious disease outbreaks, acts of terrorism, social unrest, or financial disasters in addition to natural hazards can all lead to large-scale consequences for the nation and its communities. Communities and the nation thus face difficult fiscal, social, cultural, and environmental choices about the best ways to ensure basic security and quality of life against hazards, deliberate attacks, and disasters. Beyond the unquantifiable costs of injury and loss of life from disasters, statistics for 2011 alone indicate economic damages from natural disasters in the United States exceeded $55 billion, with 14 events costing more than a billion dollars in damages each. One way to reduce the impacts of disasters on the nation and its communities is to invest in enhancing resilience—the ability to prepare and plan for, absorb, recover from and more successfully adapt to adverse events. Disaster Resilience: A National Imperative addresses the broad issue of increasing the nation's resilience to disasters. This book defines "national resilience", describes the state of knowledge about resilience to hazards and disasters, and frames the main issues related to increasing resilience in the United States. It also provide goals, baseline conditions, or performance metrics for national resilience and outlines additional information, data, gaps, and/or obstacles that need to be addressed to increase the nation's resilience to disasters. Additionally, the book's authoring committee makes recommendations about the necessary approaches to elevate national resilience to disasters in the United States. Enhanced resilience allows better anticipation of disasters and better planning to reduce disaster losses-rather than waiting for an event to occur and paying for it afterward. Disaster Resilience confronts the topic of how to increase the nation's resilience to disasters through a vision of the characteristics of a resilient nation in the year 2030. Increasing disaster resilience is an imperative that requires the collective will of the nation and its communities. Although disasters will continue to occur, actions that move the nation from reactive approaches to disasters to a proactive stance where communities actively engage in enhancing resilience will reduce many of the broad societal and economic burdens that disasters can cause.
Keywords: Earth Sciences; Policy for Science and Technology; Conflict and Security Issues

Pathways to Urban Sustainability: Challenges and Opportunities for the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Cities have experienced an unprecedented rate of growth in the last decade. More than half the world’s population lives in urban areas, with the U.S. percentage at 80 percent. Cities have captured more than 80 percent of the globe’s economic activity and offered social mobility and economic prosperity to millions by clustering creative, innovative, and educated individuals and organizations. Clustering populations, however, can compound both positive and negative conditions, with many modern urban areas experiencing growing inequality, debility, and environmental degradation. The spread and continued growth of urban areas presents a number of concerns for a sustainable future, particularly if cities cannot adequately address the rise of poverty, hunger, resource consumption, and biodiversity loss in their borders. Intended as a comparative illustration of the types of urban sustainability pathways and subsequent lessons learned existing in urban areas, this study examines specific examples that cut across geographies and scales and that feature a range of urban sustainability challenges and opportunities for collaborative learning across metropolitan regions. It focuses on nine cities across the United States and Canada (Los Angeles, CA, New York City, NY, Philadelphia, PA, Pittsburgh, PA, Grand Rapids, MI, Flint, MI, Cedar Rapids, IA, Chattanooga, TN, and Vancouver, Canada), chosen to represent a variety of metropolitan regions, with consideration given to city size, proximity to coastal and other waterways, susceptibility to hazards, primary industry, and several other factors.
Keywords: Environment and Environmental Studies

Transportation Systems for Livable Communities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Conference Proceedings on the Web 6: Transportation Systems for Livable Communities summarizes the results of an October 2010 conference that explored the challenges of incorporating livability into transportation programs and projects.The proceedings consist of presentation summaries from the opening sessions and panels, and summaries of key research needs and possible performance measures identified in the discussion groups.
Keywords: Transportation and Infrastructure

Pathways to Urban Sustainability: Research and Development on Urban Systems: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
More than half of the world's people now live in cities. In the United States, the figure is 80 percent. It is worthwhile to consider how this trend of increased urbanization, if inevitable, could be made more sustainable. One fundamental shortcoming of urban research and programs is that they sometimes fail to recognize urban areas as systems. Current institutions and actors are not accustomed to exploring human-environment interactions, particularly at an urban-scale. The fact is that these issues involve complex interactions, many of which are not yet fully understood. Thus a key challenge for the 21st century is this: How can we develop sustainable urban systems that provide healthy, safe and affordable environments for the growing number of Americans living in cities and their surrounding metropolitan areas? To address this question, the National Research Council organized a workshop exploring the landscape of urban sustainability research programs in the United States. The workshop, summarized in this volume, was designed to allow participants to share information about the activities and planning efforts of federal agencies, along with related initiatives by universities, the private sector, nongovernmental groups, state and local agencies, and international organizations. Participants were encouraged to explore how urban sustainability can move beyond analyses devoted to single disciplines and sectors to systems-level thinking and effective interagency cooperation. To do this, participants examined areas of potential coordination among different R&D programs, with special consideration given to how the efforts of federal agencies can best complement and leverage the efforts of other key stakeholders. Pathways to Urban Sustainability offers a broad contextual summary of workshop presentations and discussions for distribution to federal agencies, regional organizations, academic institutions, think tanks and other groups engaged in urban research.
Keywords: Environment and Environmental Studies

Underground Engineering for Sustainable Urban Development - National Research Council (The National Academies Press, 2013)
For thousands of years, the underground has provided humans refuge, useful resources, physical support for surface structures, and a place for spiritual or artistic expression. More recently, many urban services have been placed underground. Over this time, humans have rarely considered how underground space can contribute to or be engineered to maximize its contribution to the sustainability of society. As human activities begin to change the planet and population struggle to maintain satisfactory standards of living, placing new infrastructure and related facilities underground may be the most successful way to encourage or support the redirection of urban development into sustainable patterns. Well maintained, resilient, and adequately performing underground infrastructure, therefore, becomes an essential part of sustainability, but much remains to be learned about improving the sustainability of underground infrastructure itself. At the request of the National Science Foundation (NSF), the National Research Council (NRC) conducted a study to consider sustainable underground development in the urban environment, to identify research needed to maximize opportunities for using underground space, and to enhance understanding among the public and technical communities of the role of underground engineering in urban sustainability. Underground Engineering for Sustainable Urban Development explains the findings of researchers and practitioners with expertise in geotechnical engineering, underground design and construction, trenchless technologies, risk assessment, visualization techniques for geotechnical applications, sustainable infrastructure development, life cycle assessment, infrastructure policy and planning, and fire prevention, safety and ventilation in the underground. This report is intended to inform a future research track and will be of interest to a broad audience including those in the private and public sectors engaged in urban and facility planning and design, underground construction, and safety and security.
Keywords: Engineering and Technology

Livable Cities of the Future: Proceedings of a Symposium Honoring the Legacy of George Bugliarello - National Academy of Engineering (The National Academies Press, 2014)
At the beginning of the 20th century an estimated five percent of the world's population lived in cities. Today, half the world's population is urbanized. Urban sustainability is multifaceted and encompasses security, economics, environment and resources, health, and quality of life. It can be viewed as the intersection of two extremely complex and not yet fully understood processes, urbanization and global sustainability, which will increasingly overlap as urban populations continue to grow. Effective policies are critical for addressing urban sustainability, and must be politically realistic in deciding on appropriate balances, such as centralized versus decentralized systems, "soft" versus "hard" solutions, local versus regional focus, agriculture versus pollution, and free markets versus interventions. Livable Cities of the Future, a symposium honoring the legacy of George Bugliarello, was hosted October 26, 2012, by the Polytechnic Institute of New York University (NYU-Poly) in the Pfizer Auditorium of the Bern Dibner Library of Science and Technology. The event brought together more than 200 engineers, civic leaders, educators, and futurists to discuss how George Bugliarello's vision manifests itself in innovative urban planning for the cities of tomorrow. This report is a summary of the presentations and discussion at that event. The symposium objectives were to cultivate ideas for best practices and innovative strategies for sustainable urban development and to facilitate the evolution of New York City to a real-life laboratory for urban innovation. Participants heard the perspectives and experiences of representatives from private and public service operators, infrastructure agencies, and the academic community. Elected officials and other stakeholders in urban and other sectors examined issues critical to resilient and sustainable cities, such as energy, water supply and treatment, public health, security infrastructure, transportation, telecommunications, and environmental protection.
Keywords: Engineering and Technology

Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 767: Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas presents prototype best management practices (BMPs) for the removal of dissolved metals in stormwater runoff.The report presents three conceptual configurations in detail: two vault system configurations for urban and rural settings, and an inlet scupper with media for bridge deck drainage systems.The report also includes standard protocols to accurately measure the levels of dissolved metals in stormwater. Practical guidance on the use of these protocols is provided in an appendix to the final report. The report is accompanied by an Excel spreadsheet on CD designed to assist in sizing the filter bed in the vaults and the bridge deck inlet scupper.The CD is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD from an ISO image are provided below.Help on Burning an .ISO CD ImageDownload the .ISO CD ImageCD Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Enhancing Urban Sustainability with Data, Modeling, and Simulation: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On January 30-31, 2019 the Board on Mathematical Sciences and Analytics, in collaboration with the Board on Energy and Environmental Systems and the Computer Science and Telecommunications Board, convened a workshop in Washington, D.C. to explore the frontiers of mathematics and data science needs for sustainable urban communities. The workshop strengthened the emerging interdisciplinary network of practitioners, business leaders, government officials, nonprofit stakeholders, academics, and policy makers using data, modeling, and simulation for urban and community sustainability, and addressed common challenges that the community faces. Presentations highlighted urban sustainability research efforts and programs under way, including research into air quality, water management, waste disposal, and social equity and discussed promising urban sustainability research questions that improved use of big data, modeling, and simulation can help address. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies; Surveys and Statistics

Urban Forestry: Toward an Ecosystem Services Research Agenda: A Workshop Summary - National Research Council (The National Academies Press, 2013)
Much of the ecological research in the past decades has focused on rural or wilderness areas. Today, however, ecological research has been taking place in our cities, where our everyday decisions can have profound effects on our environment. This research, or urban ecology, includes an important element, trees. Trees have had a variety of environmental benefits for our environment including the sequestering carbon, reducing urban heat island effects, providing vital habitat for wildlife, and making nature accessible. These benefits have important impacts on the physical, socio-economic, and mental health of humans as well. Being exposed to trees has been shown to enhance social cohesion, improve health and recreational opportunities, and increase real estate values. In order to gain more knowledge into this urban forestry, the National Academy of Sciences (NAS) held a workshop February 25-26, 2013. The workshop brought together more than 100 people with various interests in urban forestry research to share information and perspectives, foster communication across specific areas of ecosystem service research, and consider integrated approaches that cut across these realms. The workshop specifically examined current capabilities to characterize and quantify the benefits, key gaps in our understanding, the challenges of planning urban forests in a way that optimizes multiple ecosystem services and more. Urban Forestry: Toward an Ecosystem Services Research Agenda: A Workshop Summary presents an overview of the issues discussed by the workshop's breakout groups; summarizes presentations from the four panels which included Biophysical Services of the Urban Forest; and context for the study with introductory material from the workshop.
Keywords: Earth Sciences

Pathways to Urban Sustainability: A Focus on the Houston Metropolitan Region: Summary of a Workshop - National Research Council (The National Academies Press, 2012)
The workshop was convened to explore the region's approach to urban sustainability, with an emphasis on building the evidence base upon which new policies and programs might be developed. Participants examined how the interaction of various systems (natural and human systems; energy, water, and transportation systems) affected the region's social, economic, and environmental conditions. The objectives of the workshop were as follows: - Discuss ways that regional actors are approaching sustainability— specifically, how they are attempting to merge environmental, social, and economic objectives. - Share information about ongoing activities and strategic planning efforts, including lessons learned. - Examine the role that science, technology, and research can play in supporting efforts to make the region more sustainable. - Explore how federal agency efforts, particularly interagency partnerships, can complement or leverage the efforts of other key stakeholders. Pathways to Urban Sustainability: A Focus on the Houston Metropolitan Region: Summary of a Workshop was designed to explore the complex challenges facing sustainability efforts in the Houston metropolitan region and innovative approaches to addressing them, as well as performance measures to gauge success and opportunities to link knowledge with action. In developing the agenda, the planning committee chose topics that were timely and cut across the concerns of individual institutions, reflecting the interests of a variety of stakeholders. Panelists were encouraged to share their perspectives on a given topic; however, each panel was designed to provoke discussion that took advantage of the broad experience of the participants.
Keywords: Policy for Science and Technology; Environment and Environmental Studies

Pathways to Urban Sustainability: Perspective from Portland and the Pacific Northwest: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
Pathways to Urban Sustainability: Perspective from Portland and the Pacific Northwest is the summary of a workshop convened by the National Research Council's Science and Technology for Sustainability Program in May 2013 to examine issues relating to sustainability and human-environment interactions in the Portland metropolitan region. Topics addressed included the role of land-use restrictions on development, transportation innovations, and economic and social challenges. The speakers at the workshop used examples from Portland and the greater Pacific Northwest region to explore critical questions in finding pathways to urban sustainability. This was the third and final of a series of three place-based urban sustainability workshops - the other two workshops focused on Atlanta, Georgia and Houston, Texas. These public workshops gathered local, state, and federal officials, academics, and key stakeholders to examine how challenges due to continued growth in the regions can be addressed within the context of sustainability. For more than 40 years, the Portland Metropolitan Region has been a national leader in urban policies and investments intended to revitalize the central city and adjacent neighborhoods, preserve the environment, improve equity, and make the city more economically competitive and livable. Portland has been both emulated as path breaking and discounted as overly idiosyncratic. Among the elements contributing to Portland's success have been strong public-private partnerships, a culture of planning, and a willingness to implement diverse ideas generated by federal, state, and local agencies, academics, and the private sector. Regionally, Portland benefits from its location in the middle of the progressive Cascadia Corridor, stretching from Vancouver, British Columbia, to San Francisco, California. This report uses examples from Portland and the Northwest U.S./S.W. Canada region to explore critical questions about the future of urban sustainability. The report provides background about Portland and Cascadia, emphasizing policy innovations and lessons that are potentially transferable elsewhere; focuses on ways to leverage local success through partnerships with state and federal agencies, companies, and nongovernment organizations; examines academic and corporate scientific and engineering research that could help cities to become more sustainable; and addresses the challenging question of how resource-constrained cities can become agents for achieving broader societal goals not directly linked to their operational mandates, such as climate change mitigation, energy independence, and improvement in human health, particularly in low-income communities.
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Pathways to Urban Sustainability: The Atlanta Metropolitan Region: Summary of a Workshop - National Research Council (The National Academies Press, 2011)
The U.S. population is more than 80 percent urban. Recognizing that many metropolitan areas in the United States have been experimenting with various approaches to sustainability, and that despite the differences among regions, there are likely some core similarities and transferable knowledge, Roundtable members selected the metropolitan Atlanta, Georgia region as a case study. The Atlanta region provided a compelling example for exploring urban sustainability issues because of the region's rapid growth rate, well-documented challenges with water, land use, and transportation; and its level of engagement with federal government agencies on matters related to sustainability. Pathways to Urban Sustainability: Lessons from the Atlanta Metropolitan Region: Summary of a Workshop explores the Atlanta region's approach to urban sustainability, with an emphasis on building evidence based foundation upon which policies and programs might be developed. The two day workshop held on September 30 and October 1, 2010 examined how the interaction of various systems (natural and human systems; energy, water and transportations systems) affect the region's social, economic, and environmental conditions. The intent of this workshop summary is to analyze a metropolitan region so that researchers and practitioners can improve their understanding of the spatial and temporal aspects of urban sustainability.
Keywords: Environment and Environmental Studies; Policy for Science and Technology